Pengaruh Lingkungan Kerja dan Pengembangan Karir Terhadap Kepuasan Kerja Karyawan pada PT X - Adhimas Dylan Dwi Sulistyo; Christian Wiradendi Wolor; Nurdin Hidayat (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to determine whether there is an influence of work environment and career development on employee job satisfaction at PT X. The study uses a quantitative approach with data collection techniques through a survey method by distributing questionnaires to 65 employees with staff positions. The data analysis technique uses multiple linear analysis processed using SPSS. The results of the study indicate that work environment has a positive and significant effect on employee job satisfaction, while career development has a positive and significant effect on employee job satisfaction.